The Effect of Culturally Responsive Teaching Supported by Gamification on Students' Critical Thinking Skills - Ayu May Lestari; Kana Hidayati (Indonesian Journal of Mathematics Education, 2026)
The increasing demand for critical thinking skills in the Industrial Revolution 4.0 era highlights the need for innovative and contextually relevant teaching approaches in mathematics education. This study aims to examine the effect of a culturally responsive teaching approach supported by gamification applications on improving students' critical thinking skills. The research focuses on the topic of Systems of Linear Equations in Two Variables and integrates artifacts from the Sonobudoyo Museum in Yogyakarta to align with the local context. A quasi-experimental method with a one-group pretest-posttest design was employed. The sample consisted of 32 students selected through purposive sampling. Data were analyzed using a paired samples t-test after confirming normality (pretest p = .140 > .05; posttest p = .431 > .05). The results showed a significant improvement in students’ critical thinking skills, as indicated by a p-value of .000 < .05 and  9.993 < t-table = 3.467, leading to the rejection of H₀. The mean score increased from 22 (pretest) to 66.14 (posttest). In conclusion, the culturally responsive teaching approach supported by gamification applications significantly improves students' critical thinking skills.